Mine of the future - A mining CEO's perspective. - Musingwini, C. (The Southern African Institute of Mining and Metallurgy., 2017)
Extract from Editorial: The mining CEO of the future will be a strategist capable of navigating complex integrated stakeholder management, forging sustainable win-win partnerships, and enforcing regulatory adherence and good governance. Such a CEO is likely to succeed as he or she can enlist the support of shareholders, governments, employees, and communities that are increasingly, and rightfully, demanding to share in the benefits of the resources mined in their jurisdictions.
President's Corner: Mine of the future - A mining CEO's perspective.
President's Corner, Editorial.
Keywords: Mining CEO; Mine of the Future; SAIMM; Southern African Institute of Mining and Metallurgy; Mining Industry; Mining teaching